CHARACTERISATION AND MONITORING OF TI6AL4V (ELI) POWDER USED IN DIFFERENT SELECTIVE LASER MELTING SYSTEMS - Thejane, Kekeletso; Chikosha, Silethelwe; du Preez, Willie (The South African Journal of Industrial Engineering, 2017)
The characterisation and monitoring of Ti6Al4V (ELI) feedstock powder is an essential requirement for the full qualification of medical implants and aerospace components produced in selective laser melting systems. Virgin and reused samples of this powder were characterised by determining their physical and chemical properties through techniques complying with international standards. This paper presents the results obtained for Ti6Al4V (ELI) powder of two different particle size distributions received from the same supplier. The characteristics of these powders after several reuse cycles in two different selective laser melting systems are also presented and discussed.